Peran Akademisi dalam Pendampingan Proses Penyusunan Peraturan Desa Tentang Pelestarian Lingkungan Hidup di Desa Wilayah Kabupaten Kebumen - Kaharti, Eni (LP3M Universitas Putra Bangsa, 2022)
Abstract Village Regulations concerning Environmental Preservation are enacted with the aim of increasing public awareness and concern for protecting and preserving the environment from pollution and damage so that environmental sustainability is maintained. The purpose of assisting academics in the preparation of the Environmental Village Regulations is to explore environmental problems that exist in the villages of the Kebumen Regency area and help provide solutions/problems that allow them to be resolved by mutual deliberation. Its decisions can be obeyed and adhered to by the local community so that the objectives of drafting the Village Regulation are achieved properly.